2013
DOI: 10.1186/1471-2458-13-1071
|View full text |Cite
|
Sign up to set email alerts
|

Active lifestyles related to excellent self-rated health and quality of life: cross sectional findings from 194,545 participants in The 45 and Up Study

Abstract: BackgroundPhysical activity and sitting time independently contribute to chronic disease risk, though little work has focused on aspirational health outcomes. The purpose of this study was to examine associations between physical activity, sitting time, and excellent overall health (ExH) and quality of life (ExQoL) in Australian adults.MethodsThe 45 and Up Study is a large Australian prospective cohort study (n = 267,153). Present analyses are from 194,545 participants (48% male; mean age = 61.6 ± 10.7 yrs) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 38 publications
7
45
0
5
Order By: Relevance
“…Among the many prospectively-obtained baseline variables, three independent long-term predictors of SRH were identified, all related to the survivorsÕ baseline health status and/or lifestyle: baseline BMI, multi-morbidity, and regular participation in sports. All these factors are well-known determinants of SRH [57][58][59][60][61][62]. However, their persistent influence on perceived health status even after 23 years is an important finding of this study, clearly demonstrating the role of healthy lifestyle for future optimal health.…”
Section: Discussionmentioning
confidence: 82%
“…Among the many prospectively-obtained baseline variables, three independent long-term predictors of SRH were identified, all related to the survivorsÕ baseline health status and/or lifestyle: baseline BMI, multi-morbidity, and regular participation in sports. All these factors are well-known determinants of SRH [57][58][59][60][61][62]. However, their persistent influence on perceived health status even after 23 years is an important finding of this study, clearly demonstrating the role of healthy lifestyle for future optimal health.…”
Section: Discussionmentioning
confidence: 82%
“…There is evidence that low daily physical activity (DPA) is associated with poor QoL in older adults [9, 10]. Furthermore, previous studies of frail persons have demonstrated that muscle strength, as represented by handgrip strength [3], plays an important role regarding QoL [6, 7, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Estudios recientes en otros países han señalado la relación positiva entre AF y salud para intervalos de edad semejantes (Gebel et al, 2015;Mesters et al, 2014). Considerando otros segmentos de edad, trabajos como los de Beyer et al (2015), Campos et al (2014), Arem (2015) o Rosenkranz et al (2013) entre otros han contrastado la relación positiva entre calidad de vida y salud autopercibida con la práctica de AF. Todo ello hace hincapié en la importancia de la AF para lograr un envejecimiento saludable.…”
Section: Introductionunclassified